Interpersonal psychotherapy for depressed adolescents - Mufson, Laura (New York : The Guilford Press, 2011)
Fully revised and expanded, the second edition of this popular treatment manual incorporates a decade's worth of scientific and practical advances
1. Overview -- 2. Application of interpersonal therapy for depressed adolescents -- 3. Special issues in treating adolescents
Includes bibliographical references (p. 291-306) and index
Keywords: Adolescent psychotherapy; Depression in adolescence -- Treatment; Interpersonal psychotherapy